2020
DOI: 10.3390/toxins12120737
|View full text |Cite
|
Sign up to set email alerts
|

Bee Venom Acupuncture Attenuates Oxaliplatin-Induced Neuropathic Pain by Modulating Action Potential Threshold in A-Fiber Dorsal Root Ganglia Neurons

Abstract: Oxaliplatin is a third-generation platinum-based chemotherapeutic drug widely used in colorectal cancer treatment. Although potent against this tumor, it can induce cold and mechanical allodynia even after a single injection. The currently used drugs to attenuate this allodynia can also cause unwanted effects, which limit their use. Bee venom acupuncture (BVA) is widely used in Korean medicine to treat pain. Although the effect of BVA on oxaliplatin-induced neuropathic pain has been addressed in many studies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 49 publications
1
33
0
Order By: Relevance
“…It has been reported that 5-HT 3 receptors are mostly present in unmyelinated C-fibers of the spinal dorsal horn [ 38 ]. However, according to data obtained from others [ 6 ] and our lab [ 10 ], oxaliplatin-induced neuropathic pain is shown to be mostly mediated by myelinated A-fibers rather than by unmyelinated C-fibers [ 6 , 10 ]. Furthermore, in several studies, cold allodynia is reported to be mediated mostly by unmyelinated fibers [ 39 ].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…It has been reported that 5-HT 3 receptors are mostly present in unmyelinated C-fibers of the spinal dorsal horn [ 38 ]. However, according to data obtained from others [ 6 ] and our lab [ 10 ], oxaliplatin-induced neuropathic pain is shown to be mostly mediated by myelinated A-fibers rather than by unmyelinated C-fibers [ 6 , 10 ]. Furthermore, in several studies, cold allodynia is reported to be mediated mostly by unmyelinated fibers [ 39 ].…”
Section: Discussionmentioning
confidence: 96%
“…Oxaliplatin (Sigma Aldrich, St. Louis, MO, USA) was dissolved in a 5% glucose solution at a concentration of 2 mg/mL, as in our previous study [ 10 ]. Oxaliplatin was administered to mice intraperitoneally in an amount of 6 mg/kg.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 11 studies were published. Three reviews provided a good overview of the therapeutic effect of bee venom [ 6 , 7 , 8 ], and eight original research articles focused on bee venom, melittin, PLA 2 , and apamin [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
mentioning
confidence: 99%